MENGAPA PEMAIN MEMBELI ITEM GAME? PERAN COLLABORATION BRANDING, KEPUASAN, DAN KETERIKATAN EMOSIONAL - Farid Naufal; Roymon Panjaitan; Imam Nuryanto; Pradana Jati Kusuma (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2026)
Game collaboration branding has emerged as a significant marketing strategy influencing player purchasing behavior. This study aims to analyze the influence of collaboration branding, player satisfaction, and emotional attachment on purchase intention among Honkai: Star Rail players. 280 active members of the Pompomfess community on Platform X (Twitter) participated in a quantitative survey that was analyzed using Structural Equation Modeling–Partial Least Squares (SEMPLS). The results extend the application of the Theory of Planned Behavior to digital game consumption behavior by showing that collaboration branding, player satisfaction, and emotional attachment significantly increases purchase intention. In addition to offering useful advice for game developers and marketers in creating player-oriented brand collaboration strategies, this study conceptually advances the body of knowledge on digital consumer behavior.